THE EFFECT OF TAXPAYER UNDERSTANDING AND USE OF E-FILING ON TAXPAYER COMPLIANCE WITH TAX VOLUNTEER AS MODERATING VARIABLE - Nyoman Sentosa Hardika; I Kadek Jesta Askara; I Made Wijana (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2022)
The tax revenue that has not reached the target is due to the low level of taxpayer compliance. One of the efforts of the Directorate General of Taxes to improve taxpayer compliance is by implementing an e-filing system and assisted by the Tax Volunteer program. The purpose of this study is to examine the effect of taxpayer understanding and the use of e-filing on individual taxpayer compliance with Tax Volunteer as a moderating variable. This study analyzed primary data from questionnaires distributed to 100 individual taxpayers at Tax Volunteer assistance locations at KPP Badung Utara and KP2KP Kerobokan through e-Riset. The sampling technique used is the purposeful technique of sampling. Statistical testing to test the hypothesis using the Partial Least Square (PLS) test tool with SmartPLS 3.0. The analysis results showed that the tax payer understanding and the use of e-filing have a positive effect on taxpayer compliance. Tax Volunteer can weaken the relationship between understanding of taxpayers on taxpayer compliance. Tax Volunteer can strengthen the relationship between e-filing on taxpayer compliance.